Feasibility Analysis of Handline Fishing Equipment Case Study on Barrang Caddi Island, Sangkarrang District, Makassar City - Ishak, Andi; Fakhriyyah, Sitti; Hasani, M. Chasyim (PONGGAWA : Journal of Fisheries Socio-Economic, 2021)
The fisheries sector is a sector that has a contribution to economic development in Indonesia, this can be seen from the increase in fishery production which continues to increase from year to year. One area that has a high level of enthusiasm in fishery economic activity is Barrang Ca'di Island with the traditional system of hand line fishing on Barrang Caddi Island resulting in the inability to access fishing locations due to one of the cruising capabilities of the fleet and production costs that must be incurred by hand line fishermen, the fisherman also still maintains the pattern of economic system patterns in fishing activities as a reference material in living their daily lives, based on this the purpose of this study is to determine the level of income for production activities and the level of business feasibility of hand line fishermen for fishing. developed on Barrang Ca'di Island. The results of the study obtained the amount of income from the fishing line business, which was Rp. 88,358,140, - and showed that the line fishing business carried out by fishermen on Barrang Caddi Island was feasible to be developed with the division between revenue and costs having a value of more than one (>1 ).